Military justice : a very short introduction - Fidell, Eugene R. ([New York] : Oxford University Press, 2016)
'Military Justice' presents an accessible and honest assessment of the strengths and weaknesses of military justice in both common law countries and those with other legal traditions, with particular emphasis on the United States, the United Kingdom, and Canada. It integrates a description of the US military justice system with a comparative view of civilian and foreign models for the administration of justice, including the increasingly important focus on human rights.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 3, 2016).
Keywords: Courts-martial and courts of inquiry; Military offenses; Military law